2020
DOI: 10.7717/peerj.10386
|View full text |Cite
|
Sign up to set email alerts
|

Identification of significant genes signatures and prognostic biomarkers in cervical squamous carcinoma via bioinformatic data

Abstract: Background Cervical squamous cancer (CESC) is an intractable gynecological malignancy because of its high mortality rate and difficulty in early diagnosis. Several biomarkers have been found to predict the prognose of CESC using bioinformatics methods, but they still lack clinical effectiveness. Most of the existing bioinformatic studies only focus on the changes of oncogenes but neglect the differences on the protein level and molecular biology validation are rarely conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Although recent studies have identified several CESC, ESCA, HNSC, KIRC, LIHC, and LUAD associated diagnostic and prognostic biomarkers including different genes, such as RFC4, ADGRF4, ANXA8L1, TOP2A, HCAR3, MCM2, IRF6, and PDE2A in CESC, 27 , 28 COL1A2, DGCR8, COL1A1, POM121, TAF9, UPF3B, ZNF469, BCAP31, and COL3A1 in ESCA, 29 , 30 LAMC2, CCT3/4/5/6/7/8, and FGFR1-4 in HNSC, 31–33 PLCB2, TNFSF13B, VAV1, RAC2, and PARVG in KIRC, 34 , 35 CDC20, MTHFD1L, CDCA8, CDCA5, KIF2C, and KIFC1 in LIHC, 36 , 37 CCNB1, SPP1, TOP2A, MKI67, CHEK1, RRM2, and CDK1 in LUAD. 38 However, none of these or any other biomarkers have been generalized so far in CESC, ESCA, HNSC, KIRC, LIHC, and LUAD patients of different clinicopathological features.…”
Section: Discussionmentioning
confidence: 98%
“…Although recent studies have identified several CESC, ESCA, HNSC, KIRC, LIHC, and LUAD associated diagnostic and prognostic biomarkers including different genes, such as RFC4, ADGRF4, ANXA8L1, TOP2A, HCAR3, MCM2, IRF6, and PDE2A in CESC, 27 , 28 COL1A2, DGCR8, COL1A1, POM121, TAF9, UPF3B, ZNF469, BCAP31, and COL3A1 in ESCA, 29 , 30 LAMC2, CCT3/4/5/6/7/8, and FGFR1-4 in HNSC, 31–33 PLCB2, TNFSF13B, VAV1, RAC2, and PARVG in KIRC, 34 , 35 CDC20, MTHFD1L, CDCA8, CDCA5, KIF2C, and KIFC1 in LIHC, 36 , 37 CCNB1, SPP1, TOP2A, MKI67, CHEK1, RRM2, and CDK1 in LUAD. 38 However, none of these or any other biomarkers have been generalized so far in CESC, ESCA, HNSC, KIRC, LIHC, and LUAD patients of different clinicopathological features.…”
Section: Discussionmentioning
confidence: 98%
“…We found this trend in our research but not statistically significant. Several studies based on TCGA-CESC data have reported the relationship between TOP2A and RFC4 mRNA expression and the prognosis of cervical cancer [ 64 , 65 ]. However, there was no other evidence to support their relationship, let alone the confirmation at the protein level.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, RFC4 decreased the growth and increased the chemosensitivity of hepatocellular carcinoma cells [ 30 ]. He et al found that RFC4 was associated with significant survival in cervical squamous carcinoma [ 31 ]. In addition, RFC4 can act as a radio resistance factor in colorectal cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%